![image](https://tex.z-dn.net/?f=1%29%5C+b_2%3D6%3B%5C+q%3D-2%5C%5C%0Ab_2%3Db_1%2Aq%3D6%5C+%3D%3E%5C+b_1%3D%5Cfrac%7B6%7D%7Bq%7D%3D%5Cfrac%7B6%7D%7B-2%7D%3D-3%5C%5C%0Ab_n%3D%28-3%29%2A%28-2%29%5E%7Bn-1%7D%5C%5C%0AS_5%3D%5Cfrac%7Bb_1%2A%281-q%5E5%29%7D%7B1-q%7D%3D%5Cfrac%7B%28-3%29%2A%281-%28-2%29%5E5%29%7D%7B-2-1%7D%3D1%2B2%5E5%3D33%5C%5C%0A2%29%5C+b_3%3D-18%3B%5C+q%3D3%5C%5C%0Ab_3%3Db_1%2Aq%5E2%3D-18%5C+%3D%3E%5C+b_1%3D%5Cfrac%7B-18%7D%7B3%5E2%7D%3D%5Cfrac%7B-18%7D%7B9%7D%3D-2%5C%5C%0Ab_n%3D%28-2%29%2A3%5En%5C%5C%0AS_5%3D%5Cfrac%7B%28-2%29%2A%281-3%5E5%29%7D%7B1-3%7D%3D1-3%5E5%3D1-243%3D-242)
\ b_1=\frac{6}{q}=\frac{6}{-2}=-3\\
b_n=(-3)*(-2)^{n-1}\\
S_5=\frac{b_1*(1-q^5)}{1-q}=\frac{(-3)*(1-(-2)^5)}{-2-1}=1+2^5=33\\
2)\ b_3=-18;\ q=3\\
b_3=b_1*q^2=-18\ =>\ b_1=\frac{-18}{3^2}=\frac{-18}{9}=-2\\
b_n=(-2)*3^n\\
S_5=\frac{(-2)*(1-3^5)}{1-3}=1-3^5=1-243=-242" alt="1)\ b_2=6;\ q=-2\\
b_2=b_1*q=6\ =>\ b_1=\frac{6}{q}=\frac{6}{-2}=-3\\
b_n=(-3)*(-2)^{n-1}\\
S_5=\frac{b_1*(1-q^5)}{1-q}=\frac{(-3)*(1-(-2)^5)}{-2-1}=1+2^5=33\\
2)\ b_3=-18;\ q=3\\
b_3=b_1*q^2=-18\ =>\ b_1=\frac{-18}{3^2}=\frac{-18}{9}=-2\\
b_n=(-2)*3^n\\
S_5=\frac{(-2)*(1-3^5)}{1-3}=1-3^5=1-243=-242" align="absmiddle" class="latex-formula">